Enrollment in Private Medical Insurance and Utilization of Medical Services Among Children and Adolescents: Data From the 2009-2012 Korea Health Panel Surveys - Dong Hee Ryu; Sin Kam; Young-Taek Doo (Korean Society for Preventive Medicine, 2016)
Objectives: The purposes of this study were to examine the status of children and adolescents with regard to enrollment in private medical insurance (PMI) and to investigate its influence on their utilization of medical services. Methods: The present study assessed 2973 subjects younger than 19 years of age who participated in five consecutive Korea Health Panel surveys from 2009 to 2012. Results: At the initial assessment, less than 20% of the study population had not enrolled in any PMI program, but this proportion decreased over time. Additionally, the number of subjects with more than two policies increased, the proportions of holders of indemnity-type only ('I'-only) and of fixed amount+indemnity-type ('F+I') increased, whereas the proportion of holders with fixed amount-type only ('F'-only) decreased. Compared with subjects without private insurance, PMI policyholders were more likely to use outpatient and emergency services, and the number of policies was proportionately related to inpatient service utilization. Regarding out-patient care, subjects with 'F'-only PMI used these services more often than did uninsured subjects (odds ratio [OR], 1.69), whereas subjects with 'I'-only PMI or 'F+I' PMI utilized a broad range of inpatient, outpatient, and emergency services relative to uninsured subjects (ORs for 'I'-only: 1.39, 1.63, and 1.38, respectively; ORs for 'F+I': 1.67, 2.09, and 1.37, respectively). Conclusions: The findings suggest public policy approaches to standardizing PMI contracts, reform in calculation of premiums in PMI, re-examination regarding indemnity insurance products, and mutual control mechanisms to mediate between national health insurance services and private insurers are required.